اهمية ممارسة الرياضة المدرسية عند الاناث في الطور الثانوي - خذري محمد خليل (My University, 2023)
.......................................................................Abstract................................................................ Study Title: A study of the importance of school sports for females in the secondary stage- A field study of Souk Ahras high schools. • Objective of the study: - Identify the importance of school sports practice for females on the cognitive side from the point of view of physical education and sports teachers for secondary education. - Highlighting the importance of school sports practice among females on the psychological side from the point of view of physical education and sports teachers for secondary education. - Determine the importance of school sports practice for females on the physical side from the point of view of physical education and sports teachers for secondary education. • Study hypotheses: - School sports practice in females is important on the cognitive side. - School sports practice in females the importance of the psychological aspect. - For school sports in females, the importance of the physical aspect. • Field study procedures: Sample: The sample was taken from eighty-one (81) teachers of physical education and sports in the secondary stage - Souk Ahras - Temporal domain: It is known methodologically that the researcher determines the time period in which he went to the field, and in the current study, the research group conducted an exploratory study on physical education and sports teachers in the secondary stage - Souk Ahras - and this was limited to the period from 15/11/2022 to 18/05/2023. Spatial field: The study was carried out on high schools - Souk Ahras – • Methodology used: The descriptive survey method was used. • Tools used: We relied in our study on a questionnaire form. • Findings: The following results have been reached: - Practicing school sports in females is important on the cognitive side. - To practice school sports in females the importance of the psychological aspect. - To practice school sports in females, the importance of the physical aspect. - School sports help to easily understand other school subjects. • Conclusions and suggestions: - The professor of physical and sports education must be aware of the responsibility he has in directing students practicing sports activities towards the appropriate specialization. - Great importance must be given to the female category as a group that contains enormous energies that can be exploited and benefited from, by providing the necessary means to practice school sports. - Expanding the practice of school sports activities in various educational institutions and in various fields. .....................................................................ملخص الدراسة............................................................. عنـوان الدراسـة: أهمية ممارسة الرياضة المدرسية عند الاناث في الطور الثانوي - دراسة ميدانية لثانويات سوق اهراس -. • هـدف الدراسـة: - التعرف على اهمية الممارسة الرياضة المدرسية عند الاناث على الجانب المعرفي من وجهة نظر اساتذة التربية البدنية والرياضية للتعليم الثانوي. - ابراز اهمية الممارسة الرياضة المدرسية عند الاناث على الجانب النفسي من وجهة نظر اساتذة التربية البدنية والرياضية للتعليم الثانوي. - تحديد اهمية الممارسة الرياضة المدرسية عند الاناث على الجانب البدني من وجهة نظر اساتذة التربية البدنية والرياضية للتعليم الثانوي. • فرضـيات الدراسـة: - للممارسة الرياضة المدرسية عند الاناث اهمية على الجانب المعرفي. - للممارسة الرياضة المدرسية عند الاناث اهمية الجانب النفسي. - للممارسة الرياضة المدرسية عند الاناث اهمية الجانب البدني. • إجـراءات الدراسـة الميدانيـة : العينـة : تم أخذ العينة من واحد وثمانون (81) منأساتذة التربية البدنية والرياضية في الطور الثانوي - سوق أهراس - المجـال الـزماني : من المعروف منهجيا أن يحدد الباحث الفترة الزمنية التي نزل فيها إلى الميدان وفي الدراسة الحالية قامت مجموعة البحث بدراسة إستطلاعيةعلىأساتذة التربية البدنية والرياضية في الطور الثانوي- سوق أهراس ، وقد إقتصر هذا على الفترة الممتدة من 15/11/2022 إلى غاية 18/05/2023. المجال المكاني: تمت الدراسة على ثانويات- سوق أهراس- • المنهـج المستخـــدم : تم إستخدام المنهج الوصفي المسحي . • الأدوات المستعملـــة :إعتمدنا في دراستنا على استمارة استبيان . • النتائج المتـوصل إلـيها : لقد تم التوصل إلى النتائج التالية : - لممارسة الرياضة المدرسية عند الاناث اهمية على الجانب المعرفي. - لممارسة الرياضة المدرسية عند الاناث اهمية الجانب النفسي. - لممارسة الرياضة المدرسية عند الاناث اهمية الجانب البدني. - لممارسة الرياضة المدرسية تساعد على سهولة فهم المواد الدراسي الأخرى. • إستخـلاصات واقتراحــات: - على أستاذ التربية البدنیة والریاضیة أن یعي المسؤولية التي یمتلكها في توجیها لتلميذات الممارسات للأنشطة الرياضية نحو التخصص المناسب. - یجب إعطاء أهمیة كبیرة لفئة الإناث باعتبارها فئة تحوي طاقات هائلة یستجوب استغلالها والاستفادة منها، وذلك من خلال توفیر الوسائل اللازمة لممارسة الرياضة المدرسية. - توسيع ممارسة الأنشطة الرياضية المدرسية في مختلف المؤسسات التربوية وفي مختلفالمجالات. ....................................................................Résumé.......................................................... • Objectif de l'étude: - Comprendrel'importance de la pratique du sport scolaire chez les filles du point de vue des professeursd'éducation physique et sportive du secondaire sur le plan cognitif. - Mettreenévidencel'importance de la pratique du sport scolaire chez les filles du point de vue des professeursd'éducation physique et sportive du secondaire sur le plan psychologique. - Déterminerl'importance de la pratique du sport scolaire chez les filles du point de vue des professeursd'éducation physique et sportive du secondaire sur le plan physique. • Hypothèses de l'étude: - La pratique du sport scolaire chez les fillesestimportante sur le plan cognitif. - La pratique du sport scolaire chez les fillesestimportante sur le plan psychologique. - La pratique du sport scolaire chez les fillesestimportante sur le plan physique. • Méthodologie de l'étude sur le terrain: Échantillon : L'échantillonétaitcomposé de 81 professeursd'éducation physique et sportive du secondaire à Souk Ahras. Période : Danscetteétude, uneenquête a étémenéeauprès des professeursd'éducation physique et sportive du secondaire à Souk Ahras, sur unepériodeallant du 15 novembre 2022 au 18 mai 2023. Lieu : L'étude a étémenéedans les lycées de Souk Ahras. • Méthodeutilisée : La méthode descriptive et exploratoire a étéutilisée. • Outilsutilisés : Nous avonsutilisé un questionnaire dansnotreétude. • Résultatsobtenus : - La pratique du sport scolaire chez les fillesestimportante sur le plan cognitif. - La pratique du sport scolaire chez les fillesestimportante sur le plan psychologique. - La pratique du sport scolaire chez les fillesestimportante sur le plan physique. - La pratique du sport scolaire aide à faciliter la compréhension des autresmatièresscolaires. • Conclusions et suggestions : - Les professeursd'éducation physique et sportive doiventprendre conscience de leurresponsabilitédansl'orientation des élèvesfémininesvers des activitéssportivesadaptées. - Unegrande importance doitêtreaccordée à la catégorie des fillesentantquegroupepossédant un potentielénorme qui peutêtreexploité et utilisé. Celapeutêtreréaliséenfournissant les moyensnécessaires pour la pratique du sport scolaire. - Il convientd'étendre la pratique des activitéssportivesscolairesdansdifférentsétablissementséducatifs et dans divers domaines.
- دراسة ميدانية لثانويات سوق اهراس -